2012
DOI: 10.1039/c2nr31355c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of lipopolysaccharide-induced nitric oxide and interleukin-6 production by PEGylated gold nanoparticles in RAW264.7 cells

Abstract: While the immunogenicity and cytotoxicity of gold nanoparticles (AuNPs) are noted by many researchers, the mechanisms by which AuNPs exert these effects are poorly understood. In this study, we investigated the effects of polyethylene glycolylated AuNPs (PEG@AuNPs) on lipopolysaccharide (LPS)-induced nitric oxide (NO) and interleukin-6 (IL-6) production and the associated molecular mechanism in RAW264.7 cells. The results showed that PEG@AuNPs were internalized more quickly by LPS-activated RAW264.7 cells than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…In contrast, Liu et al 49 demonstrated that PEGylated GNPs were internalized more quickly by lipopolysaccharide-activated RAW264.7 cells than by unstimulated cells, reaching saturation within 24 h. The PEGylated GNPs enhanced LPS-induced production of NO and IL-6 and inducible nitric oxide synthase expression in RAW264.7 cells, partly by activating p38 mitogen-activated protein kinases and NF-κB pathways. Goldstein et al 50 showed that GNPs and their plasmonic excitation could activate the Nrf2-Keap1 pathway in macrophages.…”
Section: Interaction Of Gold Nanoparticles With Immune Cellsmentioning
confidence: 90%
“…In contrast, Liu et al 49 demonstrated that PEGylated GNPs were internalized more quickly by lipopolysaccharide-activated RAW264.7 cells than by unstimulated cells, reaching saturation within 24 h. The PEGylated GNPs enhanced LPS-induced production of NO and IL-6 and inducible nitric oxide synthase expression in RAW264.7 cells, partly by activating p38 mitogen-activated protein kinases and NF-κB pathways. Goldstein et al 50 showed that GNPs and their plasmonic excitation could activate the Nrf2-Keap1 pathway in macrophages.…”
Section: Interaction Of Gold Nanoparticles With Immune Cellsmentioning
confidence: 90%
“…Interestingly, gold in the form of colloid (Auranofin) was used for many years in the treatment of rheumatoid arthritis due to its ability to substantially decrease the inflammatory component of the disease (Madeira et al, 2012). AuNP show little cytotoxicity in vivo (Downs et al, 2012; Chen et al, 2013), but results in vitro have been mixed, with several studies indicating at least some immunostimulation (Du et alo., 2012; Liu et al, 2012) dependent on coating and stabilization (Hashimoto et al, 2014). Nevertheless, the feasibility of using AuNP for the inhibition of inflammatory diseases has been considered, even though the precise mechanisms relating gold with anti-inflammatory effects remain unclear (Sumbayev et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 was ∼12× more expressed than in control cells. In vitro and in vivo studies have also reported the ability of PEG-coated Au NPs (spheres) to induce some inflammatory mediators such as IL-6 (42,43). High levels of this cytokine have been related to age-related diseases, such as cancer.…”
Section: Discussionmentioning
confidence: 99%